Five-year outcomes of posterior affected-vertebrae fixation in lumbar tuberculosis patients - Qiang Liang; Qian Wang; Guangwei Sun; Wenxin Ma; Jiandang Shi; Weidong Jin; Shiyuan Shi; Zili Wang (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background Posterior instrumentation after deformity correction is an important method for reconstruction of spinal stability in the management of lumbar tuberculosis (TB). However, the commonly used methods include both long- and short-segment fixation of normal motor units. There has been no report regarding affected-vertebrae fixation of lumbar TB. Methods Data from 135 patients with lumbar TB who underwent posterior instrumentation and either affected-vertebrae fixation or short-segment fixation using a combined posterior and anterior approach were retrospectively reviewed. Among these patients, 71 cases were treated with affected-vertebrae fixation, and 64 cases were treated with short-segment fixation. Debridement, bone grafting, deformity correction, and decompression were performed within all affected segments. Operative times, intra-operative blood loss, TB cure rates, bone graft fusion rates, degree of deformity correction, neurological function, pain recovery, and complications were analyzed. Results Comparing affected-vertebrae fixation vs. short-segment fixation groups, respectively, the number of the affected segments was 107 vs. 98; average number of affected segments was 1.51 vs. 1.53; total number of fixed segments was 107 vs. 226; average number of fixed segments was 1.51 vs. 3.53; average blood loss was 726.2 ml vs. 948.5 ml; average operative time was 210.4 min vs. 270.3 min; and average hospitalization costs were 29,000 RMB vs. 42,000 RMB (all p values < 0.05). In the affected-vertebrae fixation vs. short-segment fixation groups, respectively, TB cure rates were 82.61% vs. 84.62% at 6 months after operation and 97.83% vs. 97.44% at 5 years after operation; bone fusion rates were 86.96% vs. 87.18% at 6 months after operation and 97.83% vs. 97.66% at 5 years after operation; average number of degrees of Cobb’s angle correction were 13.1° vs. 13.7°; average correction losses were 1.9° vs. 1.4°; and complication rates were 12.04% vs. 12.97% (all p values > 0.05). Conclusion Under strict surgical indications, posterior instrumentation on affected-vertebrae is a safe, effective, and feasible fixation method in the treatment of lumber TB.